Metropolis – size, function and symbolism. A quantitative text analysis of German print media for Berlin and Hamburg - Volgmann, Kati (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
As the epitome of the urban, the city type “metropolis” has been experiencing an ongoing boom for two to three decades. With a quantitative text analysis of the leading German national print media, the patterns of linguistic use for the term metropolis and for the two largest cities Berlin and Hamburg are highlighted. They are interpreted as attributions of meaning in mass media communication processes and generate a semantic field whose analysis allows declarations to be made about size, function and imagery of a metropolis over time.
Keywords: Metropolis; Lexicometry; Print media analysis; Hamburg; Berlin